L’identification Du Média D’apprentissage Utilisé Par Les Professeurs Du Français Au Lycée À Semarang Pendant La Pandemie Covid-19 - Kurniasih, Iis; Astuti, Dwi (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2021)
Abstract LÃ¢â‚¬â„¢objectif de cette recherche est de dÃƒÂ©crire les mÃƒÂ©dias dÃ¢â‚¬â„¢apprentissage utilisÃƒÂ© par les professeurs du franÃƒÂ§ais au lycÃƒÂ©e ÃƒÂ Semarang. Cette recherche est celle de descriptive qualitative. Le variable de cette recherche est les mÃƒÂ©dias dÃ¢â‚¬â„¢apprentissage utilisÃƒÂ© par les professeurs du franÃƒÂ§ais au lycÃƒÂ©e ÃƒÂ Semarang pendant la pandemie Covid-19. Les respondents de cette recherche est les professeurs du franÃƒÂ§ais au lycÃƒÂ©e ÃƒÂ Semarang. Pour obtenir des donnÃƒÂ¨s utilise la mÃƒÂ©thode dÃ¢â‚¬â„¢enquette. Les rÃƒÂ©pondants repondent aux questions ÃƒÂ Google Form. Les rÃƒÂ©sultats montrent que les mÃƒÂ©dias dÃ¢â‚¬â„¢apprentissage utilisÃƒÂ© par les professeurs du franÃƒÂ§ais sont slide PowerPoint, lÃ¢â‚¬â„¢image, le poster, la photo, enregistrement en tÃƒÂ©lÃƒÂ©chargÃƒÂ©, enregistrement fait par professeurs, la Radio, la TÃƒÂ©lÃƒÂ©vision TVRI, le vidÃƒÂ©o en tÃƒÂ©lÃƒÂ©chargÃƒÂ©, le video fait par professeurs , YouTube, le livre, le cahier, la policopiÃƒÂ¨, Zoom , Google Meeting, Microsoft Teams 365, Kahoot , Quizziz, WhatsApp. Le mÃƒÂ©dia la plus souvent utilisÃƒÂ© est WhatsApp, et puis les mÃƒÂ©dia les moins utilisÃƒÂ© sont la radio et Microsoft Teams 365. Abstract The purpose of this research is to describe the learning media used by French teachers in high school in Semarang. The approached used in this research is qualitative descriptive. The variable in this research is the learning media used by high school French teachers in Semarang during the Covid-19 pandemic. The respondents of this research are the french teachers of senior high school in Semarang. To obtain data researcher uses the anquette method. Respondents answer the question on Google Form. The results show that the learning media used by French teachers are PowerPoint slide, image, poster, photo, downloaded recording, recording made by teachers, radio, television, downloaded video, video made by teachers, YouTube, the book, the notebook, the policopiÃƒÂ¨, Zoom, Google Meeting, Microsoft Teams 365, Kahoot, Quizziz, WhatsApp. The most frequently used media is WhatsApp, and the least used ones are radio and Microsoft Teams 365.